Teatro em Belo Horizonte - 1980 a 1990: criação de um banco de dados para o estudo da produção teatral de BeloHorizonte - Geraldo Angelo Octaviano de Alvarenga (2011)
This work introduces the data, the research, the criterions definition and the methodology for the creation of a database about the theatrical production destined to the adult audience in the Minas Gerais capital during the years 1980 up to 1990. It utilizes how major source the cultural pages of the O Estado de Minas newspaper, vehicle for spreading of larger circulation in the state during the meaningful time. It also utilizes the published information for the local theater groups, the SATED-MGs(Minas Gerais artists union) database, some researchers in the history of the theater in Belo Horizonte publications, the Itaú Cultural websites virtual encyclopedia, some Ministry of Culture publications, the Belo Horizontes municipal public file, and private files listed in the references included in the end of this work. It introduces, as attachment, a table with all the theatre plays cataloged and a CD with a Microsoft Access application with the entire database.